Research, design and manufacture a prototype of solar panel cleaning system via WiFi - Phu Huynh Minh; Nguyen Thanh Tung; Diu Ngo Thi Ngoc (BIO Web of Conferences)
This paper presents research of design and manufacturing a prototype of solar panel cleaning system in Vietnam. The 2D and 3D design of this prototype is also shown in this study. The device is used to clean dust accumulated in the face of solar panels so that it can help for enhancing power efficiency of solar panels. The prototype can be controlled manually or automatically via WiFi based on options of control system. An ESP8266 NODEMCU board is used in the hardware of the controller so that it can connect to WiFi, control motors and traveling of the device. An app is set based on Blynk app to control the system via WiFi. Operators can control the system everywhere with WiFi or 5G connection. The device can help to remove dust on solar panels and enhance the power generation efficiency, reduce time, labor, keep safety for cleaning solar panels compared with manual cleaning method.